Ekstrak ikan haruan (Channa striata) meningkatkan jumlah neokapiler pada penyembuhan luka (Extract of haruan (Channa striata) increases neocapillaries count in wound healing process ) - Muhammad Reza Setiawan; Nurdiana Dewi; Ika Kustiyah Oktaviyanti (DiscoverSys Inc., 2015)
Haruan is Kalimantan’s indigenous fish which has the potency to accelerate wound healing. Haruan extract hassubstantial properties such as albumin, Zn,Cu, and Feto accelerate wound healing. The purpose of this study is to assessthe effect of haruan extract on wistar rats buccal mucosa wound healing on day 1, 3, 5, and 7 histopathologically. Thisstudy was purely experimental with pretest-posttest with control group design. Samples were divided into 4 treatmentgroups, haruan extract 25%, 50%, 100% treatment groups and aquadest treatment group as negative control, eachtreatment wasperformed for 7 days. Neocapillariescount reached its peak on day 5. Mean neocapillaries scoring of eachgroup was 12, 16.5, 18.5, 6 respectively. Two way Anova and post hoc LSD tests presented a significant differencebetween negative control and haruan extract groups. In conclusion, haruan extract treatment significantly increasedneocapillaries count in wound healing process.